In silico analysis of phytochemical compounds for optimizing the inhibitors of HMG CoA reductase - J. Mercy Jasmine and R. Vanaja (Journal of Applied Pharmaceutical Science, 2013)
HMGCoA Reductase (HMGCR), a key enzyme in the cholesterol biosynthesis, catalyzes the conversion of 3-hydroxy-3-methylglutaryl coenzyme A (HMGCoA) into mevalonate. Thus this enzyme is the target of the cholesterol-lowering drugs known as the statins. Phytoformulation1 is a polyherbal formulation consists of the extracts of plant constituents. The present study was designed to examine the ability of the secondary metabolites of Phytoformulation 1 as an antagonist to HMGCoA reductase enzyme by in silico molecular docking. The docking analysis was carried out by Ligand Fit Accelry’s Discovery studio 2.1, which allows virtual screening of database of compounds and predict the strongest binders based on various scoring functions. Fifteen ligands were docked with HMG CoA reductase receptor, out of which four compounds Dichloroacetic acid 2, 2-dimethylpropyl ester, 1, 6, 10-Dodecatriene-3-ol, 3, 7, 11-trimethyl-[S-(Z)]-, Isopropyl acrylate and 3, 3-Dimethylacryloyl chloride were able to form hydrogen bonds with active site of target protein. Thus it may be concluded that the secondary metabolites of Phytoformulation 1 can be an inhibitor of the HMGCR receptor that could be used to treat hyperlipidemia and further in vivo studies may be carried out to prove the same.
Keywords: HMG CoA Reductase, Molecular docking, Hyperlipidemia